Fabrication of poly (lactic acid)/hydroxyapatite (PLA/HAp) porous nanocomposite for bone regeneration. (1st January 2015) - Thanh, Dinh Thi Mai; Trang, Pham Thi Thu; Huong, Ho Thu; Nam, Pham Thi; Phuong, Nguyen Thu; Trang, Nguyen Thi Thu; Hoang, Thai; Lam, Tran Dai; Seo–Park, Jun
In this study, a poly (lactic acid)/hydroxyapatite (PLA/HAp) porous nanocomposite was fabricated by melt mixing method. Polyethylene oxide (PEO) was added into the nanocomposite to improve compatibility of HAp in the PLA matrix. A porous structure of the nanocomposite was created by using a salt (NaCl) which leaches in water. The influence of HAp's weight, compatibiliser content of porous agent on morphology and mechanical properties of PLA/HAp nanocomposite was investigated by SEM and tensile testing method. The obtained results indicated that the nanocomposite containing 20 wt% HAp, 5 wt% PEO, and an amount of NaCl in proportion with PLA weight (1 : 1) had good mechanical properties with a promising Young's modulus close to the one of cancellous bone (530 MPa) as well as a high porosity. The invitro tests of nanocomposite in simulated body fluids (SBF) were carried out and then pH of SBF solution, variation of material mass (Δm), morphology and phase structure of the nanocomposite were also estimated. The results showed that pH decreased, and Δm had positive or negative values depending on composition and surface of material formed by HAp crystals and the hydrolysis of PLA during immersion time.